2011
DOI: 10.1152/ajpregu.00633.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated normobaric hypoxia exposures during sleep on acute mountain sickness, exercise performance, and sleep during exposure to terrestrial altitude

Abstract: Fulco CS, Muza SR, Beidleman BA, Demes R, Staab JE, Jones JE, Cymerman A. Effect of repeated normobaric hypoxia exposures during sleep on acute mountain sickness, exercise performance, and sleep during exposure to terrestrial altitude. Am J Physiol Regul Integr Comp Physiol 300: R428 -R436, 2011. First published December 1, 2010; doi:10.1152/ajpregu.00633.2010.-There is an expectation that repeated daily exposures to normobaric hypoxia (NH) will induce ventilatory acclimatization and lessen acute mountain sick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 26 publications
2
65
0
Order By: Relevance
“…Studies have reported conflicting results regarding intermittent normobaric or hypobaric hypoxic exposures, with some studies showing benefit [107] and others not demonstrating a clear effect [108,109]. One of the challenges in interpreting these discrepant results is that the hypoxic exposure protocols vary significantly between studies with regard to the magnitude and duration of the hypoxic exposures.…”
Section: Preacclimatisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported conflicting results regarding intermittent normobaric or hypobaric hypoxic exposures, with some studies showing benefit [107] and others not demonstrating a clear effect [108,109]. One of the challenges in interpreting these discrepant results is that the hypoxic exposure protocols vary significantly between studies with regard to the magnitude and duration of the hypoxic exposures.…”
Section: Preacclimatisationmentioning
confidence: 99%
“…While these preacclimatisation strategies may carry benefit and probably pose little risk, implementation may be difficult for many travellers and the optimal approach remains unclear. Infrequent and/or short exposures to hypoxia are unlikely to reduce the incidence of AMS [109,110], while longer and/or more frequent exposures are necessary to reduce the risk of altitude illness [107,111]. Such exposures should be performed as close in time to the planned high-altitude travel as possible.…”
Section: Preacclimatisationmentioning
confidence: 99%
“…The effect of intermittent hypoxia (normobaric) and its physiological outcome during subsequent exposure to actual field condition (hypobaric hypoxia) is scanty. Schommer 22 , et al studied the normobaric hypoxia exposure of 14 h -18 h in 12 per cent -16 per cent O 2 for 70-90 min per day at the rate of 3 days per week for four weeks along with an overnight stay at 3611 m on arterial blood gases or AMS during subsequent hypobaric hypoxia residence at 4559 m. The effect of repeated normobaric hypoxia exposure in un-acclimatised sea level residents during sleep for 7.5 h in each night for seven consecutive days on acute mountain sickness and sleep during subsequent exposure to hypobaric hypoxia at 4350 m altitude showed significantly higher SaO 2 and AMS upon awakening was lower 18 . Our study is also first to report where volunteers breathed normobaric hypoxia air (12 % F I O 2 ) for four hours per day for four consecutive days on acute mountain sickness at 3500 m high altitude.…”
Section: Discussionmentioning
confidence: 96%
“…The studies on the effect of (IHE) at sea level and its possible outcomes on reducing the susceptibility to AMS during subsequent high altitude sojourn are very limited. Only two laboratory based studies have showed a significant reduction in the incidence and severity of AMS after IHE at sea level in laboratory based condition 17,18 . The effect of intermittent hypoxia (normobaric) and its physiological outcome during subsequent exposure to actual field condition (hypobaric hypoxia) is scanty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation